The use of novel mechanical devices for enhancing the performance of railway vehicles - Alejandra Z. Matamoros-Sanchez (2013)
Following successful implementation of inerters for passive mechanical control in racing cars, this research studies potential innovative solutions for railway vehicle suspensions by bringing the inerter concept to the design of mechatronic systems. The inerter is a kinetic energy storage device which reacts to relative accelerations; together with springs and dampers, it can implement a range of mechanical networks distinguished by their frequency characteristics. This thesis investigates advantages of inerter-based novel devices to simplify the design of active solutions. Most of the research work is devoted to the enhancement of vertical ride quality; integrated active-plus-novel-passive solutions are proposed for the secondary suspensions. These are defined by different active control strategies and passive configurations including inerters. By optimisation of the suspension parameters, a synergy between passive and active configurations is demonstrated for a range of ride quality conditions. The evidence of cooperative work is found in the reduction of the required active forces and suspension travelling. This reveals a potential for reducing the actuator size. Benefits on power requirements and actuator dynamic compensation were also identified. One of the strategies features a nonlinear control law proposed here to compensate for 'sky-hook' damping effects on suspension deflection; this, together with inerter-based devices attains up to 50% in active force reduction for a setting providing 30% of ride quality enhancement. The study is developed from both, an analytical and an engineering perspective. Validation of the results with a more sophisticated model is performed. The lateral stability problem was briefly considered towards the end of the investigation. A potential use of inerter-based devices to replace the static yaw stiffness by dynamic characteristics was identified. This leads to a synergy with 'absolute stiffness', an active stability solution for controlling the wheelset 'hunting' problem, for reducing the creep forces developed during curve negotiation.